EFFECT OF CATALYST IN SYNTHESIS POLYOL CORE OF OIL SEEDS KENARI (Canarium commune) METHOD EPOXIDATION - ., Murniati; Seno Handayani, Sri (Jurnal Lembaga Penelitian Universitas Mataram, 2014)
Research has been done on the effect of catalyst type polyol synthesis of walnut kernel oil epoxidation method in order to know whether the walnut kernel oil can be used as raw material for making polyols with epoxidation method, determine the effect of catalyst on the synthesis of polyol type and the nature of the physico-chemical polyol formed. From the research, walnut kernel oil can be used as raw material for the manufacture of polyols with a way to transform core walnut methyl ester into polyols via epoxidation reactions. Retrieved changes in physico-chemical properties of methyl ester polyol core walnut into the dark yellow to yellow clear the HCl catalyst and Bentonite and dark yellow color on H2SO4 catalyst, iodine number of 107.45 mg iodine/g to 84.22 mg of methyl ester iodine/g polyol H2SO4, 66.92 mg iodine/g polyol HCl, and 30.82 mg iodine/g polyol bentonite. Percent (%) conversion of polyols derived polyol H2SO4 was 24.47%, 39.98% HCl polyols and polyols 72.36 bentonite. While the viscosity of the oil to be produced polyol is 0.61 cSt (oil), 1.13 cSt (polyol H2SO4), 1.22 cSt (polyol HCl), and 1.83 cSt (polyol bentonite).